Importance of reporting survival as incidence: a cross-sectional comparative study on out-of-hospital cardiac arrest registry data from Germany and Norway. Issue 2 (17th February 2022) - Tjelmeland, Ingvild Beathe Myrhaugen; Alm-Kruse, Kristin; Grasner, Jan-Thorsten; Isern, Cecilie Benedicte; Jakisch, Barbara; Kramer-Johansen, Jo; Renzing, Niels; Wnent, Jan; Seewald, Stephan
Abstract : Objectives: Health registries are a unique source of information about current practice and can describe disease burden in a population. We aimed to understand similarities and differences in the German Resuscitation Registry (GRR) and the Norwegian Cardiac Arrest Registry (NorCAR) and compare incidence and survival for patients resuscitated after out-of-hospital cardiac arrest. Design: A cross-sectional comparative analysis reporting incidence and outcome on a population level. Setting: We included data from the cardiac arrest registries in Germany and Norway. Participants: Patients resuscitated between 1 January 2015 and 31 December 2019 were included, resulting in 29 222 cases from GRR and 16 406 cases from NorCAR. From GRR, only emergency medical services (EMS) reporting survival information for patients admitted to the hospital were included. Primary and secondary outcome measures: This study focused on the EMS systems, the registries and the patients included in both registries. The results compare the total incidence, incidence of patients resuscitated by EMS, and the incidence of survival. Results: We found an incidence of 68 per 100 000 inhabitants in GRR and 63 in NorCAR. The incidence of patients treated by EMS was 67 in GRR and 53 in NorCAR. The incidence of patients arriving at a hospital was higher in GRR (24.3) than in NorCAR (15.1), but survival was similar (8 in GRR and 7.8 in NorCAR). Conclusion: GRR is a voluntary registry, and in-hospital information is not reported for all cases. NorCAR has mandatory reporting from all EMS and hospitals. EMS in Germany starts treatment on more patients and bring a higher number to hospital, but we found no difference in the incidence of survival. This study has improved our knowledge of both registries and highlighted the importance of reporting survival as incidence when comparing registries.